Kesiapsiagaan Komunitas Sekolah Menghadapi Bencana Melalui Group Supportive Therapy dan Pelatihan Sekolah Siaga - Renidayati Renidayati; Reflita Reflita; Zolla Amely Ilda; Yessi Fadriyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to implement the group supportive therapy model and Disaster Preparedness School training to increase school community preparedness for disasters on the coast of West Sumatra. This research method is quantitative research with a quasi-experimental pre-post test research design without a control group. The results of the study's first phase showed an increase in preparedness for potential disasters of 23,614 students. The group supportive therapy model and disaster preparedness training program effectively increase school preparedness for potential disasters by 62.71%. In conclusion, there are differences in the increase in readiness for possible earthquake and tsunami disasters in elementary school students before and after being given a group supportive therapy model and disaster preparedness training with a group that only received disaster preparedness training. Keywords: Disaster Preparedness School, Supportive Therapy